PERAMALAN PERMINTAAN DAN SIMULASI DALAM IMPLEMENTASI METODE MRP TERHADAP PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA MENU ICE COFFEE LATTE DI CAFÉ CASPER AND LUNA - Muhammad Rafii Lisdiarto (2022)
The development of the café business in Indonesia is growing very rapidly, and it is necessary to have supplies in order to continue to meet the needs of consumers. One of the café industries is Café Casper and Luna. The beverage menu that is quite influential is the Ice Coffee Latte. The operational process of Café Casper and Luna does not use mathematical calculations in controlling inventory. The purpose of this study is to determine the optimal inventory cost by using Material Requirement Planning (MRP) in order to reduce the nominal inventory cost which begins with a forecasting calculation and aggregate planning and is supported by Monte Carlo Simulation activities. In addition, the results from the simulation are also used for further calculations to be compared later with the results from forecasting data. The result of this research is that the most effective demand forecasting method is the Moving Average with a MAD value of 32,89, MSE of 1456,25, and MAPE of 14,39%. The results of the simulation show a total error of 0,23% with the average of the estimated simulation and 4,09% with the results of the forecast. These results indicate that the results of the simulation are valid and reliable enough. Aggregate planning calculations chosen to be used is the Chase Strategy method for forecasting data and Level Strategy for simulation data with values of Rp45.803.334 and Rp48.479.265, respectively. The final result, the most effective method is the Lot for Lot method using data from forecasting results. This method is suitable because the error rate of the forecasting is more relevant and the number on hand and the frequency of ordering is less with a total cost of raw material inventory for Coffee Beans of Rp3.278.375, Brown Sugar of Rp1.498.333, Milk of Rp2.505.167, and Ice Cubes of Rp313.866.